Islamic capital markets : products and strategies - Hassan, Kabir M.; Mahlknecht, Michael (Wiley finance series, 2011)
"This book covers all Islamic derivatives and structured products including state of the art Islamic short-selling methods used by hedge funds and gives a comprehensive overview of current Islamic capital markets. It takes a practical approach addressing practical issues in risk management and investing for both Islamic and non-Islamic readers"--Provided by publisher